The resurrection of Jesus in history and faith: an investigation of two critical approaches to the Easter Kerygma in the New Testament - McDonald, Ronald Lee (The University of Edinburgh, 1976)
Christianity makes its boldest claim when it speaks about a God who acts in time and space events in history such as in the Exodus or the resurrection of Jesus from the dead. This claim has always been a part of the Christian message; but since the time of the Enlightenment and the development of the historical -critical method, it has become the focal point of numerous debates among Christian theologians. Does God in fact work in ways which can be observed, detected, or experienced through the sensory perceptions of man? Is it conceivable that God would intervene in history by raising someone from the dead?

The primary purpose of this thesis is first of all to point out some of the problems which the modern approach to history poses for Christian faith and then to set forth an alternative approach to the biblical message of God's unique activity in Jesus Christ which will be both meaningful and a challenge to modern man. Rudolf Bult- mann's radical application of the historical -critical method to the biblical writings and his resultant negative approach to miracles or the supernatural events recorded in Scripture has been most helpful in clarifying some of the major problems which face the Church in a secular society today. He has raised the question of the relevance of all such supernatural talk for modern man and has attempted to translate the message of the New Testament into meaningful twentieth - century language. Whether or not he has adequately translated the Church's Easter message and how well he has handled the New Testament traditions which confess the resurrection of Jesus will be explored in Part One of this thesis.

It will be shown in Part One that Bultmann's understanding of the Easter message has been greatly influenced by his understanding of history and how this understanding has guided him to an inappropriate interpretation of the Resurrection narratives.

In Part Two of the thesis, the writer will offer an alternative approach to history which will appreciate the uniqueness of God's activity in raising Jesus from the dead and also set forth another interpretation of the Resurrection narratives. It will be argued that the most appropriate way of examining the Easter faith of the earliest Christian community begins with an open view of history which does not rule out either in principle or methodology the uniqueness of God's activity in history. Following this, a study will be made of the problems of harmony and coherence in the Resurrection narratives and an attempt made to clarify their message.

Before bringing the thesis to a conclusion, a final chapter will be added which will briefly examine the primary arguments generally used to support the case for the resurrection of Jesus from the dead. It will be shown there that the "case" cannot be based so much upon "air- tight" historical arguments as upon the religious pre- suppositions which are derived from Christian experience with the Risen Christ.

Through this study it is hoped that a more meaningful confes- sion of the resurrection of Jesus will be set forth which will, on the one hand, appreciate the value of salvation history and, on the other, emphasize the significance of the Easter event in the Church's theology. It is also hoped that through this work a contribution will be made toward a better understanding of the problems in the Resurrection narratives.